Efficacy of traditional practices and botanicals for the control of termites on rice at Ikene, southwest Nigeria - Nwilene, F.E.; Agunbiade, T.A.; Togola, M.A.; Youm, O.; Ajayi, O.; Oikeh , S.O.; Ofodile , S.; Falola, O.O. (Springer, 2008)
Upland rice is mostly at risk from soil-borne insect pests, including termites, which cause significant crop yield losses. Studies were conducted in 2005 and 2006 at Ikenne, southwest Nigeria to assess the effectiveness of two traditional practices (cow dung and red palm oil mixed with pawpaw), two plant extracts (neem seed oil and neem powder) and Furadan coated with garri (cassava flour) against termite attacks on nine rice varieties—NERICAs 1–7, LAC 23 and OS 6. In 2005, the results showed that neem seed oil was more effective than neem powder and cow dung in the control of termites. Of the five treatments in 2006 (Furadan coated with garri, neem seed oil, neem powder, cow dung and red palm oil mixed with pawpaw), two treatments—neem seed oil and Furadan coated with garri—gave the best protection against termite attack. Among the rice varieties, termite attack was significantly lower on NERICA 5 than on the other NERICA varieties in both years. NERICA 5 was apparently the least attacked by termites when unprotected, indicating that it could be used as a resistant check variety for termites. Yield losses were lower in the treated than in the control plots. These findings indicate that botanicals, such as neem seed oil, can provide effective control against termites on rice fields and can also be used as alternatives to persistent chemical pesticides. This study has far-reaching implications because neem seed oil is environmentally safe, easy to prepare, readily available and affordable by resource-poor farmers in Nigeria.